1978
DOI: 10.1002/1520-6807(197807)15:3<349::aid-pits2310150306>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the WISC-R and PPVT for a group of mentally retarded students

Abstract: This study compared the WISC-R and PPVT scorm for a grou of 65 students classified as mentally retarded, ranging in age from 7.5 to 14.5. $earson product momenta (r) and correlated t values were em loyed in the analysis of data. The evidence from the present study indicatefthat for this sample of mildly retarded children and youth, the PPVT I& score is si ificantly higher than the Full Scale I& from the WISC-R. The current fintifngs indicate that the same general pattern exists for the WISC-R and PPVT as for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The revision and restandardization of this instrument suggest that the PPVT-R, unlike the PPVT, may be more consistent with other comparably standardized tests that measure verbal comprehension. Despite the fact that the PPVT has correlated significantly with the WISC-R Verbal I& and Stanford-Binet (Concannon, 1975;Covin, 1976Covin, , 1977aCovin, , 1977bGroden, Branson, & Mann, 1976;Richmond & Long, 1977;Ritter, Duffey, & Fischman, 1974;Vance, Prichard, & Wallbrown, 1978) the mean PPVT often has been significantly different from the mean Stanford-Binet and Wechsler IQs (Covin, 1976;Gensemer, Walker, & Cadman, 1976;Hodapp & Hodapp, 1980;Vance et al, 1978). Only a few studies have examined the relationship between the PPVT-R and intelligence tests.…”
mentioning
confidence: 99%
“…The revision and restandardization of this instrument suggest that the PPVT-R, unlike the PPVT, may be more consistent with other comparably standardized tests that measure verbal comprehension. Despite the fact that the PPVT has correlated significantly with the WISC-R Verbal I& and Stanford-Binet (Concannon, 1975;Covin, 1976Covin, , 1977aCovin, , 1977bGroden, Branson, & Mann, 1976;Richmond & Long, 1977;Ritter, Duffey, & Fischman, 1974;Vance, Prichard, & Wallbrown, 1978) the mean PPVT often has been significantly different from the mean Stanford-Binet and Wechsler IQs (Covin, 1976;Gensemer, Walker, & Cadman, 1976;Hodapp & Hodapp, 1980;Vance et al, 1978). Only a few studies have examined the relationship between the PPVT-R and intelligence tests.…”
mentioning
confidence: 99%
“…Previous studies have been conducted to determine the comparability of scores attained on the PPVT and the WISC-R. These studies have demonstrated consistently that the PPVT overestimates the intellectual abilities of EMR individuals by approximately 6 to 12 IQ points as measured by the WISC-R (Covin, 1976;Hodapp & Hodapp, 1980;Vance, Prichard, & Wallbrown, 1978). The PPVT has been revised recently (PPVT-R; Dunn, 1980) and will no doubt continue to be used with EMR individuals.…”
mentioning
confidence: 99%
“…In the main, past research has provided little consensus as to the underlying constructs of the PPVT with learning-problem children (Anderson & Flax, 1968; Shaw, Matthews, & Klove, 1966;Taylor, 1975). Furthermore, the majority of studies reviewed based conclusions upon less than 100 subjects (Covin, 1976;Gensemer et al, 1976; Kimbrell, 1960; Shaw et al, 1966; Vance, Prichard, & Wallbrown, 1978). These small numbers offered little variation in the populations, ages, and grade levels studied and, thus, little generalizability.…”
mentioning
confidence: 99%